PENGARUH MODEL PEMBELAJARAN GAME BASED LEARNING (GBL) BERBANTUAN APLIKASI WORDWALL TERHADAP HASIL BELAJAR SISWA PADA MATERI PECAHAN KELAS III DI SDN 8 SYAMTALIRA ARON - Soraya; Rahmi Wahyuni; Friantiani Safitri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study focuses on the low and uninnovative mathematics learning outcomes of third-grade students regarding fractions at SDN 8 Syamtalira Aron. This study aims to identify the effect of the Game Based Learning (GBL) model assisted by the Wordwall application on student learning outcomes. The method used in this study is quantitative experimental with a Non-equivalent Control Group Design. The research sample includes an experimental class (III-A, n=18) and a control class (III-B, n=17). Data were obtained through written tests (pre-test and post-test) and analyzed using the non-parametric Mann-Whitney U statistical test because the data were not normally distributed. The results of hypothesis testing showed a significance value (Asymp. Sig. 2-tailed) of 0.003 < 0.05, so Ha is accepted. The results of data analysis showed that the post-test average of the experimental class (94.47) was significantly higher than that of the control class (75.37). The conclusion of this study indicates that the use of the GBL model assisted by the Wordwall application has a significant effect on improving student learning outcomes in fraction materials in third grade at SDN 8 Syamtalira Aron.